FAKTOR-FAKTOR YANG MEMPENGARUHI PENDUDUK LANJUT USIA MEMILIH UNTUK BEKERJA - Moch. Affandi (Journal of Indonesian Applied Economics, 2009)
This  study analysis  the determinant of  the old generations workers (more  than 60years old) to work or to enter teh labour market. Using Sakerti data, it can be seenthat they have low level of education, low level of family expenditure, are living inthe rural area and working in the informal sector. Generally, the condition of familyeconomy  is  the main  determinant  for  old  generation workers  to work  or  join  thelabour market. Therefore, there is a need to prepare the work conditions and activi-ties that fit for old generation workers due to the fact they are not productive any-more in term of employment.Keywords: old generation workers, labour market and informal sector